The i-FSC proxy for predicting inter-event and spatial variation of topographic site effects - Aline Bou Nassif; Emeline Maufroy; Pascal Lacroix; Emmanuel Chaljub; Mathieu Causse; Pierre-Yves Bard (Bulletin of Earthquake Engineering, 2025)
Our study focuses on predicting topographic amplification of ground motion in the near-source region, where seismic rays reach the free-surface at varying incidence angles. We rely on data from previous 3D numerical simulations conducted on a topographic relief with a homogeneous medium. First, using neural networks, we identify which key parameters, describing the geometric characteristics of the relief relative to the seismic source position, control ground motion amplification. Then, we determine the functional form that relates these parameters to the simulated amplifications. Subsequently, we conduct a regression study to develop a model of topographic amplification, referred to as the i-FSC proxy (Illuminated Frequency-Scaled Curvature). Our estimator depends on the frequency-scaled (1) curvature, a parameter that accounts for the occurrence of amplifications over convex topographies and de-amplification over concave ones; (2) normalized illumination angle, a newly defined parameter that quantifies the slope exposure to the incoming wavefield, accounting for high amplification on slopes oriented opposite to the seismic source. The illumination parameter reduces the uncertainties of the proxy by a factor of 2 compared to estimators that rely solely on curvature. The proxy does not require high computational resources. It uses a digital elevation map and a seismic source position to predict amplification factors (without lithological effects) for an S -wave at any site on the surface topography. It allows exploration of variations in topographic amplification near seismic sources, representing a significant breakthrough as areas closest to the fault typically sustain the highest damages. A MATLAB script performing the i-FSC calculations is provided.

Optimization of a Simulation Code Coupling Extended Source (k−2) and Empirical Green’s Functions: Application to the Case of the Middle Durance Fault - Alain Dujardin; Fabrice Hollender; Mathieu Causse; Catherine Berge-Thierry; Bertrand Delouis; Laetitia Foundotos; Gabriele Ameri; Hussein Shible (Pure and Applied Geophysics, 2020)
We developed a ground-motion simulation code base on extended rupture modeling combined with the use of empirical Green’s functions (EGFs), adapted for low-to-moderate seismicity regions (with a limited set of EGFs), and extended its range of applicability to the lowest source-to-site distances. This code is based on a kinematic source description of an extended fault and is designed to allow complex fault geometries and to generate a ground motion variability in agreement with that of the recorded databases. The code is developed to work with a sparse set of EGFs. Each available EGF is therefore used in several positions on the rupture area. To be used in positions different of their original position, we applied to the EGFs some adjustments. In addition to the classical adjustments (i.e. time delay correction, geometrical spreading correction and anelastic attenuation correction), we propose here a radiation pattern adjustment. The effectiveness of it is tested in a numerical application. We showed noticeable improvements at the lowest distances, and some limitations when approaching the nodal planes of the subevents the recording of which were used as EGFs. We took advantage of the development of this code, its ability to work with a sparse set of EGFs, its ability to take into account complex fault geometries and its ability to master the general variability, to perform a ground-motion simulation scenario on the Middle Durance Fault (MDF). We perform simulations for a hard rock site (V S30 = 1800 m/s) and a sediment site (V S30 = 440 m/s) of the CEA Nuclear Research Site of Cadarache (France), and compared the computed ground motion with several ground motion prediction equations (GMPEs). The GMPEs slightly underestimate the sediment site but strongly overestimate the ground motion amplitude on the hard rock site, even when using a specific correction factor which adapts GMPEs predictions from rock site to hard rock site. This general ascertainment confirms the need to continue efforts towards the establishment of consistent GMPEs applicable to hard-rock conditions.

Near-Fault Broadband Ground Motion Simulations Using Empirical Green’s Functions: Application to the Upper Rhine Graben (France–Germany) Case Study - Sergio Del Gaudio; Sebastien Hok; Gaetano Festa; Mathieu Causse; Maria Lancieri (Pure and Applied Geophysics, 2017)

Ground motion prediction in Beirut: a multi-step procedure coupling empirical Green’s functions, ground motion prediction equations and instrumental transfer functions - Marleine Brax; Mathieu Causse; Pierre-Yves Bard (Bulletin of Earthquake Engineering, 2016)

Simulation of the Basin Effects in the Po Plain During the Emilia-Romagna Seismic Sequence (2012) Using Empirical Green’s Functions - Alain Dujardin; Mathieu Causse; Françoise Courboulex; Paola Traversa (Pure and Applied Geophysics, 2016)

Eurocode 8-compatible synthetic time-series as input to dynamic analysis - Mathieu Causse; Aurore Laurendeau; Matthieu Perrault; John Douglas; Luis Fabian Bonilla; Philippe Guéguen (Bulletin of Earthquake Engineering, 2014)